Upper Washita River Experimental Watersheds: Nutrient Water Quality Data. Issue 4 (1st July 2014) - Starks, P. J.; Steiner, J. L.; Moriasi, D. N.; Guzman, J. A.; Garbrecht, J. D.; Allen, P. B.; Naney, J. W.
Abstract : Climate variability, changing land use and management, and dynamic policy environments are the main reasons why long‐term research is needed to understand and predict possible water quality outcomes to alternative future scenarios. Long‐term water quality data sets are needed to address these water issues. Such data sets were acquired by the USDA–ARS in three watersheds in Oklahoma: the Southern Great Plains Research Watershed (SGPRW), the Little Washita River Experimental Watershed (LWREW), and the Fort Cobb Reservoir Experimental Watershed (FCREW). We provide: (i) a description of these water quality data sets, (ii) the sample collection and processing procedures used and an assessment of the data quality, (iii) summary analyses of the variability in each data set, and (iv) details about how to access these data sets. Water quality data collection in the SGPRW began in the 1960s and continued through 1978, while that in the LWREW covered the 1960s to 1990 period. Data collection began in the FCREW in 2004 and continues through the present. The data were collected from streams, unit source watersheds, groundwater wells, and reservoirs. The water quality data described for a given site are generally complete for a given period of record; however, not all sites were monitored continuously and were not necessarily analyzed for the same water quality parameters. These data sets are expected to improve modeling and assessments of conservation practices in relation to climate variability, land use changes, and other environmental factors and may be useful in developing strategies to mitigate these environmental impacts.